The generalized mathematical model of space-optical transformation of angular speed and the moment of inertia in problems of the analysis and synthesis - Vedmitskyi, Yu. H.; Kukharchuk, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The generalized mathematical model of spatial-optical transformation of the angular speed and the moment of inertia rotating bodies is designed. It is shown that the offered model can be used to solve problems of the analysis and synthesis of converter elements structure.